2003
DOI: 10.1152/ajpendo.00436.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 5′AMP-activated protein kinase activity and substrate utilization in exercising human skeletal muscle

Abstract: The metabolic role of 5ЈAMP-activated protein kinase (AMPK) in regulation of skeletal muscle metabolism in humans is unresolved. We measured isoform-specific AMPK activity and ␤-acetyl-CoA carboxylase (ACC␤) Ser 221 phosphorylation and substrate balance in skeletal muscle of eight athletes at rest, during cycling exercise for 1 h at 70% peak oxygen consumption, and 1 h into recovery. The experiment was performed twice, once in a glycogen-loaded (glycogen concentration ϳ900 mmol/kg dry wt) and once in a glycoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
312
5
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(342 citation statements)
references
References 60 publications
20
312
5
5
Order By: Relevance
“…Indeed substantial experimental evidence in humans supports this. For example, when exercise is commenced in the glycogen depleted state the phosphorylation of AMPK is greater in the post exercise recovery when muscle glycogen is low [21][22][23]. Interestingly, in rodent studies when exercise occurs in the low glycogen state AMPK nuclear content is increased [24].…”
Section: The Molecular Regulation Of Endurance Training Adaptation Ementioning
confidence: 99%
“…Indeed substantial experimental evidence in humans supports this. For example, when exercise is commenced in the glycogen depleted state the phosphorylation of AMPK is greater in the post exercise recovery when muscle glycogen is low [21][22][23]. Interestingly, in rodent studies when exercise occurs in the low glycogen state AMPK nuclear content is increased [24].…”
Section: The Molecular Regulation Of Endurance Training Adaptation Ementioning
confidence: 99%
“…During states of low energy, such as muscle contraction or exercise, it is widely accepted that liver kinase B1 (LKB1) acts as an upstream AMPK kinase that phosphorylates and activates AMPK and initiates a multitude of signaling events to maintain energy homeostasis (39 -41). Although strong evidence indicates that the LKB1-AMPK cascade is a key signaling pathway that regulates changes in glucose uptake, fatty acid (FA) uptake, and FA oxidation in contracting skeletal muscle (16,25,54,56), data also show that AMPK may not be the sole signal mediating contractioninduced changes in glucose uptake, FA uptake, and FA oxidation (35,36,56).Along with AMPK, mounting data suggest that increases in intracellular Ca 2ϩ concentration ([Ca 2ϩ ]) may play a key role in the regulation of glucose uptake, FA uptake, and FA oxidation in skeletal muscle and that this may occur in part via AMPK activation (3,28,51,53,56,57). There is evidence that Ca 2ϩ /calmodulin-dependent protein kinase (CaMK) kinase (CaMKK) activates AMPK in vitro in cells, whole skeletal muscle, and yeast (17,20,21,55), and we recently showed that activation of CaMKK and CaMKII leads to activation of AMPK in perfused rat hindlimbs (1, 35).…”
mentioning
confidence: 99%
“…During states of low energy, such as muscle contraction or exercise, it is widely accepted that liver kinase B1 (LKB1) acts as an upstream AMPK kinase that phosphorylates and activates AMPK and initiates a multitude of signaling events to maintain energy homeostasis (39 -41). Although strong evidence indicates that the LKB1-AMPK cascade is a key signaling pathway that regulates changes in glucose uptake, fatty acid (FA) uptake, and FA oxidation in contracting skeletal muscle (16,25,54,56), data also show that AMPK may not be the sole signal mediating contractioninduced changes in glucose uptake, FA uptake, and FA oxidation (35,36,56).…”
mentioning
confidence: 99%
“…The ratio between fat and carbohydrate oxidation during exercise depends on preexercise substrate levels and exercise duration and intensity (12,40,42,44). However, the intracellular determinants of the use of these fuels are unclear.…”
mentioning
confidence: 99%